Call Me Tom : The Life of Thomas F. Eagleton - Giglio, James N., 1939- (Book collections on Project MUSE., 2011)
Detailed biography of the St. Louis senator as a moderate liberal in a conservative state, from a promising attorney to contributions in environmental and social legislation. Known for his successful bipartisanship, he was the Democratic nominee for Vice-President in 1972 until personal problems were revealed.